Work-related psychosocial risks and mental health of youths during the COVID-19 pandemic - Syed Ismail, Sharifah Norkhadijah; Rasdi, Irniza; Chong, Harry Wai Soon; Shamsuddin, Aida Soraya (Universiti Putra Malaysia, 2024)
Introduction: Youth represent a significant part of the workforce globally. This study aimed to determine the effects of work-related psychosocial risk factors on mental health of working youth during the Covid-19 pandemic. Materials and methods: A cross-sectional survey was conducted from August to October 2021 on 307 working youths in Klang Valley, Malaysia. The Copenhagen Psychosocial Questionnaire version three (COPSOQ-III) and 7-item Generalized Anxiety Syndrome (GAD-7) were used to assess work-related psychosocial risk factors and mental health problems symptoms. Statistical analysis followed by Spearman correlation and multiple linear regression analysis were performed to determine associations between the variables. Results: The results showed most of the working youth experienced low workplace bullying, moderate workload, work-pace and work-life conflict, high support from supervisors and colleagues, and severe job insecurity. Most of the respondents had moderate sleep disturbance (55.0%), burnout (56.7%), stress (45.0%), depressive symptoms (59.0%), and anxiety (38.1%). Correlation between work-pace and stress show strong correlation with ρ = .623 (p < .001). The work-pace, work-life conflict, workplace bullying, and job insecurity accounted for approximately 37.5% of the variance in stress (Adjusted R2 = .375, F (4,302) = 46.913, p < .001). Limitation: This study's limitations include the use of self-reported data from respondents, which makes misclassification feasible, and its cross-sectional design. Conclusion: Work-pace was identified as the strongest contributor to stress among working youth. The findings can be used by employers to raise the performance, commitment, and response of their workers to the Covid-19 pandemic by controlling work-pace, flexible work schedules, and mental health assistance.